2015
DOI: 10.1002/chem.201504315
|View full text |Cite
|
Sign up to set email alerts
|

A Hexameric Cationic Copper(II) Metallacrown as a Pertechnetate and Perrhenate Scavenger

Abstract: Materials based on the cationic copper(II) hexanuclear 18-membered metallacrown [18-MCCuII-N(2ph)-6](6+) (2phH=2-piconyl hydrazide) and tetrafluoroborate, perchlorate, nitrate, sulfate, and perrhenate anions were prepared by an easy method in aqueous medium. Single-crystal X-ray characterization of six members of this new family of complexes showed that the anions are attached to the metallacrown by direct coordination to a copper cation or by hydrogen-bonding interaction with the center of the hexamer. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…A similar phenomenon also occurs when 2 reacts with NH 3 (aq) at RT generating trans-[Ru II (tda-κ-N 3 )(py) 2 (NH 3 )], 4, (Scheme 1), whereupon NH 3 coordinates to Ru and the tda 2− ligand decreases its coordination mode from κ-N 3 O to κ-N 3 as can be observed in Figure 1 (Supporting Information Figure S12). Interestingly, the reaction of 2 with hydrazine also produces the coordination at the equatorial position, accompanied by a formation of a new C(O)−N bond between the hydrazine and the carboxylate, thus generating an unusual acyl hydrazine derivative, 57 trans-[Ru II (tda-κ-N 3 )(N-NH 2 )-(py) 2 ], 5, as outlined in Scheme 1 and proved by the X-ray diffraction crystal structure presented in Figure 1 (Supporting Information Figure S13).…”
Section: Methodsmentioning
confidence: 99%
“…A similar phenomenon also occurs when 2 reacts with NH 3 (aq) at RT generating trans-[Ru II (tda-κ-N 3 )(py) 2 (NH 3 )], 4, (Scheme 1), whereupon NH 3 coordinates to Ru and the tda 2− ligand decreases its coordination mode from κ-N 3 O to κ-N 3 as can be observed in Figure 1 (Supporting Information Figure S12). Interestingly, the reaction of 2 with hydrazine also produces the coordination at the equatorial position, accompanied by a formation of a new C(O)−N bond between the hydrazine and the carboxylate, thus generating an unusual acyl hydrazine derivative, 57 trans-[Ru II (tda-κ-N 3 )(N-NH 2 )-(py) 2 ], 5, as outlined in Scheme 1 and proved by the X-ray diffraction crystal structure presented in Figure 1 (Supporting Information Figure S13).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, small cationic metal–organic complexes have been reported to sense or immobilize TcO 4 – /ReO 4 – , but they all lack extended structures, resulting in high solubility in aqueous solution. , Fei et al first reported a cationic layered [Ag 2 (4,4′-bipy) 2 (O 3 SCH 2 CH 2 SO 3 )·4H 2 O] (SLUG-21) MOF material for the efficient removal of ReO 4 – . The sorption process represented a new paradigm for anion separation entitled single-crystal-to-single-crystal transformation, giving a high sorption capacity of 602 mg/g for ReO 4 – .…”
Section: Pertechnetate Separation Materialsmentioning
confidence: 99%
“…In used nuclear fuel and high-level radioactive waste, technetium-99 ( 99 Tc), which is a β-emitter with a long half-life of 2.13 × 10 5 years, is one of the most-problematic radionuclides. 1 With a high fission yield of ∼6%, 21 kg of 99 Tc is annually produced by a 1 GWe-scale nuclear reactor, leading to a large inventory of ∼155 tons accumulated over the past 20 years all over the world. 2 99 Tc predominately exists in the form of the pertechnetate anion (TcO 4 − ) in both the nuclear fuel cycle and environments under oxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the long-lived radioactive nuclides, β-emitting radionuclide 99 Tc with a long half-life of 2.13 × 10 5 years and the fission yield as high as about 6% has lasting impacts on the environment and human health and is recognized as one of the most problematic radionuclides. , It primarily exists as 99 Tc­(VII) in the form of 99 TcO 4 – under aerobic conditions. , Because of large solubility in water (11.3 mol/L for its sodium salt, 20 °C) and nearly noncomplexing nature, TcO 4 – has extremely high mobility in the environment. , Besides, the generation of volatile Tc 2 O 7 during the vitrification process of nuclear waste increases the difficulty of handling 99 Tc. Therefore, to mitigate long-term nuclear waste storage issues, it is necessary that 99 Tc should initially be removed from the nuclear waste before vitrification, followed by transmutation into short-lived or stable nuclides, such as ruthenium isotopes. , …”
Section: Introductionmentioning
confidence: 99%